Editorial – Revista Ambiente Contábil – Volume 11 – Número 2 – Ano 2019 (Jul./Dez. 2019) - Maurício Corrêa da Silva (Revista Ambiente Contábil, 2019)
Editorial – Revista Ambiente Contábil – Volume 11 – Número 2 – Ano 2019 (Jul./Dez. 2019)